Electronic systems - Bolton, W. (William), 1933- (Bolton, W. (William), 1933- Study topics in physics, 1980)
Electronic Systems is concerned with electronic systems such as sine-wave oscillators, amplifiers with negative feedback, operational amplifiers, analogue and digital computers, switching circuits, bistable circuits, and microprocessors. This text is comprised of five chapters; the first of which introduces the basic ideas of a system, feedback, control, and logic gates. Examples of feedback and closed-loop control are given, and the distinction between the effects of positive and negative feedback is described, along with the functions of AND, OR, NOT, NOR, and NAND logic gates. The next chap.